Ebola virus disease in pregnancy: a systematic review and meta-analysis. (2nd December 2021) - Kayem, Nzelle D; Benson, Charlotte; Aye, Christina Y L; Barker, Sarah; Tome, Mariana; Kennedy, Stephen; Ariana, Proochista; Horby, Peter
Abstract: This review synthesises and appraises evidence on the effects of Ebola virus disease (EVD) in pregnancy. We searched bibliographic databases from dates of inception to November 2020, yielding 28 included studies. The absolute risk of maternal death associated with EVD was estimated at 67.8% (95% confidence interval [CI] 49.8 to 83.7, I 2 =85%, p<0.01) and the relative risk of death in pregnant women compared with non-pregnant women was estimated at 1.18 (95% CI 0.59 to 2.35, I 2 =31.0%, p=0.230). The absolute risk for foetal losses was estimated at 76.9% (95% CI 45.0 to 98.3, I 2 =96%, p<0.01) and neonatal death was 98.5% (95% CI 84.9 to 100, I 2 =0.0%, p=0.40). The gap analysis suggests limited or no data on the clinical course, non-fatal perinatal outcomes and EVD management in pregnant women. The review suggests that EVD has a high maternal and perinatal mortality, underscoring the urgent need for preventative and therapeutic solutions and improved screening and follow-up of pregnant women and newborns during outbreaks. There is not enough evidence to conclusively rule out pregnancy as a risk factor for mortality and there is limited evidence on the disease course, outcomes and management of EVD in pregnancy, and this supports the need for robust clinical trials and prospective studies that include pregnant women.